MQTT in Action: Building Reliable and Scalable Home Automation Systems - Bilal Raslen; Maysaa Salama (Sakarya University Journal of Computer and Information Sciences)
This study presents the development and implementation of an MQTT-based home automation system, emphasizing its reliability, scalability, and efficiency. The system integrates the ESP8266 microcontroller with various sensors, including IR, temperature, DHT11, sound, and vibration sensors. Leveraging the lightweight MQTT protocol for real-time data transmission and PostgreSQL for robust data storage, the system monitors environmental conditions, detects specific events, and performs appropriate actions. Performance tests indicate the system maintains low response times, high data accuracy, and exceptional reliability, making it a viable solution for modern smart homes. The findings suggest that the system enhances security, optimizes energy usage, and improves overall comfort for homeowners. Future research will focus on enhancing the security of the MQTT protocol against spoofing attacks through the integration of AI for threat detection and blockchain technology for enhanced data security.